ANALISIS STRATEGI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH AL HUDA CABANG KALIWIRO DALAM MENEKAN NON PERFORMING FINANCING - Rizqa Wahyu adiba; Muhammad Mathori (Jurnal Riset Manajemen Akuntansi Indonesia, 2026)
This study aims to analyze the factors contributing to the high level of Non-Performing Financing (NPF) at KSPPS Al Huda Kaliwiro Branch, determine the institution's strategic position through SWOT analysis, and formulate strategies to maintain the NPF level below the healthy threshold (<5%). This research employed a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation involving managers, financing staff, and the institution's financial records. The findings indicate that the main causes of NPF can be categorized into two aspects: internal and external factors. Internal factors include weaknesses in financing feasibility analysis and inadequate post-disbursement monitoring. External factors consist of member dishonesty, poor business management, and the impact of local economic conditions. Based on the SWOT analysis, KSPPS Al Huda is positioned in Quadrant I (aggressive strategy), indicating that the institution possesses strong internal strengths and significant external opportunities. The recommended strategies include improving the quality of financing analysis based on the 5C+1S principle, strengthening the monitoring system, optimizing the restructuring of problematic financing, and implementing financial literacy programs for members.